EEC-Urgency of monetary integration - Andreas Predöhl (Intereconomics, 1971)
For many years, the guardians of the world's currency system have tried to cure the symptoms of its illness. They were not even altogether unsuccessful in their attempts to maintain the system of Bretton Woods. But its shortcomings are still conspicuous. One crisis after another occurs, and the fear lest the system which is tied to the US dollar disintegrate has never faded.
Keywords: 330; International Monetary Policy